Immigration and the Health of Older Natives in Western Europe - José J. Escarce; Lorenzo Rocco (Global Labor Organization (GLO), 2018)
Previous research has found that immigration benefits the health of working-age natives, an effect mediated through the labor market. We use the Study of Health, Ageing and Retirement in Europe (SHARE) to investigate whether immigration also affects the health of natives 65-80 years old. Immigration may increase the supply and lower the price of personal and household services, a term that refers to care services and non-care services such as cleaning, meal preparation, and domestic chores. Higher consumption of personal and household services by older natives may help maintain health through a variety of pathways. Using a shift-share IV, we find pervasive beneficial effects of immigration on the physical and mental health of older natives. We also find evidence for the hypothesized pathways, especially for an effect of immigration in increasing social integration (e.g., institutional connections, social participation). However, our ability to test mechanisms is limited in our data.
Keywords: I12; I14; J61; 330; Health; immigration; aging; social determinants